“New doesn’t mean better”: Towards a new concept of innovative health technology - Fiestas, Elmer (2022)
An innovative health technology (IHT) should be understood as a new technology that is better in its benefits than the status quo in the local health system. The additional benefit that the IHT means must refer to relevant outcomes for a society based on complete best quality scientific evidence. This proposed definition of IHT then highlights the social value of a health technology, which can be made explicit through that methodological tool, increasingly used globally, called health technology assessment. This approach can help governments, from an ethical and economic perspective, to ensure a more efficient distribution of resources and public budgets for rapid and equitable access of the population to IHT. This article proposes and supports the implementation of this definition of IHT in the decision-making processes in health in the Peruvian context.